Laiduntamisen tehokkuuteen vaikuttavat tekijät - Virkajärvi, Perttu; Sairanen, Auvo; Nousiainen, Jouni I; Järvenranta, Kirsi (Suomen Nurmiyhdistys, 2001)
FACTORS AFFECTING GRAZING EFFICIENCY Perttu Virkajärvi, Auvo Sairanen, Jouni Nousiainen & Kirsi Järvenranta MTT, North Savo Research Station, Halolantie 31 A, FIN-71750 Maaninka Grazed grass forms the second largest proportion of forage used in the dairy sector in Finland. Well managed pasture has a high feeding value and in the same time it is the cheapest forage available. This presentation considers the most important factors that affect pasture utilization. The presented results are based on experiments carried out at MTT in 1995-2000. Experiments were carried out on winter calving Friesian dairy cows. The pastures were a mixtures of timothy and meadow fescue. Nitrogen fertilization rate was in the range of 190 - 220 kg/ha depending on the year. The effect of herbage allowances (HA) of 19, 23 and 27 kg dry matter (DM) per cow per day was studied in 1998. Increasing HA increased milk yields linearly by 0.16 kg energy corrected milk (ECM) per extra kg HA. Simultaneously, pasture utilization decreased by 2 %-units per each extra kg HA. Although increasing HA decreased post-grazing herbage mass, it had no effect on subsequent regrowth rate. The effect of HA is linked to concentrate use and vice versa. In practice, it is impossible to allocate daily pasture area by measuring herbage mass, but the post-grazing sward height of 8 - 10 cm is a reasonable indicator of suitable pasture utilization. The feeding value of pasture is an important factor affecting pasture utilization. In spring the organic matter digestibility (OMD) of pasture remains high even till early stem formation. However, when 2 or 3 nodes are formed at the lower part of the stem the OMD decreases sharply and milk yields of the cows will drop accordingly. Furthermore, the stem becomes rigid, which lead to increased DM losses (up to 50 % measured to 5 cm cutting height). Leaf content of pasture is related to herbage OMD, but in a different way compared to more southern countries, e.g Ireland. Concentrates can be used to increase milk yields of cows but also to manipulate pasture rotation, especially during periods of slow pasture growth. Experiment with concentrate levels of 0, 3, 6 and 9 kg commercial concentrate /cow/day shoved a mean response of 0.7 kg ECM per kg concentrate. Simultaneously pasture utilization decreased by 2 %-units per kg concentrates, since HA was fixed at the level of 21 kg/cow/day. The substitution effect of 0.6 kg decrease in herbage intake per kg concentrate is affected by HA and pasture quality. The effect itself is important when concentrates are given to substitute pasture shortage and to slow down pasture rotation. Grazing season should be fully utilized. This requires early turn-out of cows in spring. In experiment carried out in 1997 the difference of only 5 days in turn-out day led to better pasture quality, higher milk yield per cow, easier pasture management and 14% higher energy output per hectare. In general, annual forages e.g. Italian ryegrass, can be used to balance the poor growth of timothy in mid and late summer. As conclusion, the efficiency of grazing can be increased often without high economic inputs. It can be done through careful planning, precise pasture allocation, reasonably use of concentrates and early turn-out day. The economic effect is dependent on individual farm and the level of EU subsidies.
Factors affecting grazing efficiency
Keywords: Ka; laidun; laiduntaminen; lypsykarja; grazing; pastures; dairy cows